Current opportunities of management of innovative complex of human capital - Pavluik, Tetiana (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The paper purpose is study modern forms and methods of managing the formation and development of available human capital of the enterprise. Design/methodology/approach. The basic principles of the study are structural-functional analysis, system-comparative and analytical methods. Also, the method of analysis and synthesis, expert, and abstract-logical were used. Findings. The subject of the study provides recommendations on the use of modern human capital management tools in order to increase its innovation. These recommendations can be used in practical activities of Ukrainian enterprises, in order to increase the efficiency of using human capital and increase profits of organizations, thanks to the use of the latest innovative production technologies. Research limitations/implications. The article clearly identifies the main modern methods of management of innovative human capital in order to increase the efficiency of its use and improve its quality. Originality/value. The scientific significance of the article is the study of modern methods of managing the innovative component of human capital, in order to increase the efficiency of the use of available human capital.